A randomised phase II study of modified FOLFIRINOX versus gemcitabine plus nab-paclitaxel for locally advanced pancreatic cancer (JCOG1407). (March 2023) - Ozaka, Masato; Nakachi, Kohei; Kobayashi, Satoshi; Ohba, Akihiro; Imaoka, Hiroshi; Terashima, Takeshi; Ishii, Hiroshi; Mizusawa, Junki; Katayama, Hiroshi; Kataoka, Tomoko; Okusaka, Takuji; Ikeda, Masafumi; et al.
Abstract: Aim: We compared the efficacy of modified 5-fluorouracil, leucovorin, irinotecan, and oxaliplatin (mFOLFIRINOX) with that of gemcitabine plus nab-paclitaxel (GnP) for locally advanced pancreatic cancer (LAPC). Methods: Patients with untreated LAPC were randomly assigned (1:1) to receive mFOLFIRINOX or GnP. One-year overall survival (OS) was the primary endpoint. The major secondary end-points included progression-free survival (PFS), response rate (RR), carbohydrate antigen 19-9 (CA19-9) response, and adverse events. The sample size was 124 patients to select a more effective regimen with a minimum probability of 0.85 and to examine the null hypothesis of the 1-year OS <53%. Results: Of the 126 patients enrolled from 29 institutions, 125 were deemed eligible. The 1-year OS was 77.4% (95% CI, 64.9–86.0) and 82.5% (95% CI, 70.7–89.9) in the mFOLFIRINOX and GnP arms, respectively. The median PFS was 11.2 (95% CI, 9.9–15.9) and 9.4 months (95% CI, 7.4–12.8) in the mFOLFIRINOX and GnP arms, respectively. The RR and CA19-9 response rate were 30.9% (95% CI, 19.1–44.8) and 57.1% (95% CI, 41.0–72.3) and 42.1% (95% CI 29.1–55.9) and 85.0% (95% CI, 70.2–94.3) in the mFOLFIRINOX and GnP arms, respectively. Grade 3–4 diarrhoea and anorexia were predominant in the mFOLFIRINOX arm. Conclusion: GnP was considered the candidate for a subsequent phase III trial because of its better RR, CA19-9 response, and mild gastrointestinal toxicities. Both regimens displayed higher efficacy in the 1-year survival than in the historical data of gemcitabine monotherapy. Highlights: Pancreatic cancer is one of the most fatal cancers worldwide. We compared the efficacy of mFOLFIRINOX with that of GnP in LAPC. mFOLFIRINOX and GnP achieved similar efficacy. Both regimens showed better 1-year survival than gemcitabine monotherapy. GnP demonstrated better DCR and CA19-9 response and mild gastrointestinal toxicity.